SEISMIC HAZARD ASSESSMENT FOR THE CORINTH GULF AND CENTRAL IONIAN ISLANDS BY MEANS OF THE LINKED STRESS RELEASE MODEL - Mangira, O.; Papadimitriou, E.; Tsaklidis, G.; Vasiliadis, G. (Bulletin of the Geological Society of Greece, 2016)
Εarthquake generation causes spatio-temporal stress changes on adjacent fault segments that can alter the occurrence probability of subsequent earthquakes onto them. The interaction is investigated with the Linked Stress Release Model, applied to fit historical data from two areas that accommodate high seismicity, the Corinth Gulf and the Central Ionian Islands. These two areas are divided in two subareas, based on seismotectonic features; Corinth Gulf is divided in the western and eastern part, whereas the area of Central Ionian Islands is divided in Kefalonia and Lefkada subareas. The results establish interactions between the subareas, especially in the Central Ionian Islands, and underline the differences in tectonic structures and earthquake mechanisms between these areas. Particularly, the seismicity in the Central Ionian Islands is proved to be more complex and active and yet more difficult to be examined, whereas the LSRM fits the Corinth Gulf data more easily.